2018
DOI: 10.1007/s00402-018-3046-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of posttraumatic arthritis following distal radius fractures in non-osteoporotic patients and the association with radiological measurements, clinician and patient-reported outcomes

Abstract: IntroductionOutcomes of non-osteoporotic patients who sustained a distal radius fracture (DRF) have not gained much attention in recent literature. The aims of this study were to determine the prevalence of posttraumatic arthritis (PA), to analyze associations of radiological measurements, clinician-reported and patient-reported outcomes (CROs and PROs) with PA and gain insight into employment changes after DRF in non-osteoporotic patients.MethodsNon-osteoporotic patients following a DRF were selected. Radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 67 publications
0
24
1
Order By: Relevance
“…The treatment options for DRFs have vastly improved over the years. Beginning with conservative treatment including closed reduction and plaster casts [1][2][3][4][5][6][7][8], K-wires were the first invasive method of stabilization. They were partly used in combination with external fixation.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment options for DRFs have vastly improved over the years. Beginning with conservative treatment including closed reduction and plaster casts [1][2][3][4][5][6][7][8], K-wires were the first invasive method of stabilization. They were partly used in combination with external fixation.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that grip strength is merely a reflection of overall muscle strength and condition of a chain of muscles in the upper limb and at longterm follow-up is not severely impacted by hand or wrist injury [52][53][54]. In contrast, range of motion is significantly impacted by hand and wrist injuries and influences fine tactile functioning [53][54][55]. Therefore, we hypothesize that arm/shoulder problems impact heavy lifting activity, but to a lesser extent fine tactile functioning.…”
Section: Discussionmentioning
confidence: 93%
“…For example, all DIF results for location of complaint indicated that among patients with the same overall level of UE functioning, patients with only hand/wrist injuries indicated more problems with activities that involve fine tactile functioning and patients with only shoulder problems indicated more problems with activities involving heavy lifting tasks, reaching above shoulder level or behind the back. It is known that grip strength is merely a reflection of overall muscle strength and condition of a chain of muscles in the upper limb and at longterm follow-up is not severely impacted by hand or wrist injury [52][53][54]. In contrast, range of motion is significantly impacted by hand and wrist injuries and influences fine tactile functioning [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…A main indication for arthroscopy in DRFs is an intra-articular step or gap from 1 to 2 mm after closed reduction [5], which is a prognostic factor for post traumatic osteoarthritis [16,17]. Arthroscopically assisted treatment of DRFs can help detecting and treating scaphoid fractures and/or ligament injuries.…”
Section: Indicationsmentioning
confidence: 99%